An exploration into caring for a stroke-survivor in Lima, Peru: Emotional impact, stress factors, coping mechanisms and unmet needs of informal caregivers - Pesantes M.A. (2017)
Understanding local complexities and challenges of stroke-related caregiving are essential to develop appropriate interventions. Our study aimed to characterize the impact of post-stroke care among informal caregivers in a setting of transitioning economy.